Burden of acute lymphoblastic leukemia in children and adolescents in low- and middle-income countries from 1990 to 2023 and projections to 2050: A systematic analysis from the global burden of disease study 2023 - Peng Liu; Zixin Xu; Wenfu Song; Jianxiong Yang; Jianbao Li (PLoS ONE, 2026)
Background Acute Lymphoblastic Leukemia (ALL) is the most common and curable malignancy in children and adolescents, yet it remains a significant health threat. Despite global survival improvements driven by new drugs and treatment protocols, comprehensive data on disease burdens and attributable risk factors across diverse socio-economic contexts remain limited. This study evaluated the epidemiological characteristics, temporal trends, and modeled attributable risk factors of ALL in LMICs from 1990 to 2023. Methods Using GBD 2023 data, we analyzed ALL incidence, mortality, and DALYs in children and adolescents (0–19 years), stratified by World Bank income groups. We assessed temporal trends via Joinpoint regression, projected burdens to 2050 using the Bayesian Age-Period-Cohort (BAPC) model, and evaluated risk attribution for occupational benzene and formaldehyde exposure. Results In 2023, LMICs reported 64,477 new ALL cases and 30,909 deaths, with a higher burden in males. While the age-standardized incidence rate (ASIR) declined overall, absolute cases rose due to population growth. Although occupational benzene and formaldehyde exposure were the only modeled risk factors, their Population Attributable Fractions (PAFs) were negligible (<1%), indicating minimal contribution to the total burden. Projections suggest the age-standardized ALL burden will continue declining through 2050, with the sharpest decrease expected in low-income countries. Conclusion Globally, childhood and adolescent ALL mortality and DALYs are declining, yet the burden remains substantial in many LMICs, with the smallest improvements observed in low-income countries from 1990 to 2023. Occupational benzene and formaldehyde exposure contributed minimally to the total burden (PAFs < 1%), indicating that direct occupational exposure is rare in children. These findings suggest that the persistent burden in LMICs is primarily driven by healthcare system factors rather than occupational environmental exposures. Therefore, efforts to further reduce ALL mortality and DALYs in high-burden regions should address gaps in healthcare access and treatment delivery.